Qasidah and Dangdut as Means for Political Contest in Romansha's Kelir Slindet and Telembuk: Dangdut dan Kisah Cinta yang Keparat - Rae Shella Tivani Mareta (Universitas Brawijaya, 2023)
Qasidah and Dangdut Pantura are cultural products in the form of opposite musical arts; a paradox. Both genres are very popular in Indramayu. This paradox is narrated in the novel series entitled Kelir Slindet and Telembuk: Dangdut dan Kisah Cinta yang Keparat by Kedung Darma Romansa. Two characters (Pak Darmawan and Kaji Nasir) used Qasidah and Dangdut as political tools. This research aims to find out the factors that influence differences in public perceptions of qasidah and dangdut and how the strategies of the two characters dominate the arena. This was a qualitative descriptive study. It used the theory of Pierre Bourdieu's Habitus and Arena. The results showed that the different perspectives and choices of people in the two novels were influenced by social piety, prestige, experience, and taste. In conclusion, Pak Darmawan with his strategy using Dangdut won the village head election because Dangdut was not only considered entertainment but it depicted the culture of Indonesia.